Human Response to Cold Climate: First Evidence from the Tibetan Plateau during the Last Glacial Maximum - Wenli Li; Weijian Zhou; Peng Cheng; Peixian Shu; Yikun Li; John Dodson; Yuda Chui; Yan Hu; Ling Yang; Hua Du; Xuefeng Lu (Quaternary Science Advances)
The Tibetan Plateau (TP) is a hotspot for early human history research, however, there is no evidence of prehistoric human activity on the southern TP during the Last Glacial Maximum (LGM). Thus, it remains unclear how the cold climate affected human activities and whether humans could survive such extremes on the Tibetan Plateau. Here, we present eight AMS 14C dates obtained from charcoal at a newly discovered blade site-Pengbuwuqing (PBWQ) in the Yarlung Zangbo River Valley basin, southern TP. We have also identified ochre at Paleolithic sites on the TP for the first time. Our chronological data indicate the human occupation of the Yarlung Tsangpo River basin during MIS2 (cal 29.2–27.0 kyr B.P), (cal 25.03–24.37 kyr B.P), and (cal 23.7–23.1 kyr B.P). This site represents the first evidence of human activity during the LGM in the southern TP valley and indicates that the southern TP river valley could have served as a refugium enabling prehistoric humans to survive the cold LGM on the TP.